The effectiveness of digital training and development platforms in enhancing job competencies within the General Directorate of Public Security in the Kingdom of Saudi Arabia, according to the Kirkpatrick model (The International Journal of Educational Sciences and Arts, 2026)
The study aimed to evaluate the effectiveness of digital platforms for training and development in enhancing the job competencies of Public Security personnel through the four levels of the Kirkpatrick Model, while identifying trainees’ satisfaction with platform quality and ease of use, measuring the achievement of learning outcomes and the acquisition of new competencies through digital pathways, monitoring the transfer of training impact to actual job behavior in the field, and determining the institutional return on digital training and its contribution to achieving the Directorate’s strategic objectives, in addition to examining the effect of demographic variables (age, experience, and training courses) on the evaluation of platform effectiveness. The study adopted a descriptive–analytical survey approach, with a sample of 168 Public Security Directorate personnel who responded to the questionnaire. The results revealed a strong, positive, and statistically significant relationship between the quality of digital training platforms and employees’ job competencies, with learning and satisfaction explaining approximately 68.4% of the variance in job competency, while the majority of participants reported a high level of satisfaction with the platforms (mean score of 3.98 out of 5), indicating broad acceptance of e-training technologies. Digital training effectively contributed to developing participants’ knowledge and professional skills, particularly through the acquisition of new skills and the flexibility of self-paced learning, and its impact on job behavior was reflected in improved daily performance and the application of learned skills in practical tasks, ultimately leading to improved institutional outcomes such as increased overall efficiency, reduced errors, and the achievement of the Directorate’s objectives.
Keywords: Digital Platforms; Job Competencies; Kirkpatrick Model